Gambaran Hematologi 3 Bulan Pasca Vaksinisasi Porcine Reproductive and Respiratory Syndrome (PRRS) pada Ternak Babi di Kabupaten Kupang - Simarmata, Yohanes T. R. M. R.; Gelolodo, Maria A.; Sitompul, Yeremia Y.; Sole, Marsyella G. (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2024)
Pigs are the most commonly raised livestock in Kupang Regency, offering various advantages over other animals. However, the growing pig population poses a higher risk of diseases such PRRS, which affects both respiratory and reproductive health. Vaccination remains a crucial method for preventing PRRS. Post-vaccination haematological examinations are essential for assessing immune responses, utilizing parameters like leukocyte and lymphocyte counts to evaluate vaccine efficacy and safety. This study investigates haematological parameters as indicators of physiological responses to PRRS vaccination, a relatively less explored area compared to other immunological assessments. The research analysed haematological parameters such as RBC, HGB, PCV, MCV, MCH, MCHC, and WBC both before and three months after vaccination. Blood samples were collected from 15 pigs one day prior to and three months following vaccination. SPSS software was used to analyse the data. The results indicated that haematological parameters remained within normal ranges. RBC, HGB, PCV, and MCHC did not significantly differ, however MCH, MCV, and WBC levels did indicate statistically significant variations. These results support the safety and efficacy of PRRS immunization by indicating that it causes detectable haematological alterations. This study underscores the importance of using haematological parameters as reliable indicators for assessing vaccine pigs reaction.